Hydrogen adsorption in zeolites A, X, Y and RHO - Langmi, H; Walton, A; Al-Mamouri, M; Johnson, SR; Book, D; Speight, J; Edwards, P; Gameson, I; Anderson, P; Harris, I (2003)
We have investigated the use of zeolites as potential hydrogen storage materials. The zeolites A, X, Y and RHO, which encompass a range of different pore geometries and compositions, were synthesised by hydrothermal methods, and different cation-exchanged forms were prepared through ion-exchange from aqueous metal nitrate solutions. The phase composition and crystallinity of samples were interrogated by powder X-ray diffraction. Scanning electron microscopy revealed cubic crystals of zeolites both before and after ion-exchange. Hydrogen adsorption capacities were measured using a constant pressure Thermogravimetric Analyser; data were obtained over a range of pressures from 0 to 15 bar and isothermally at temperatures from -196 to 300 °C. The results showed that hydrogen uptake in zeolites is strongly dependent upon temperature, and also on framework and cation type. Surface area measurements were also carried out on these materials and the results used to interpret the hydrogen adsorption data. © 2003 Elsevier B.V. All rights reserved.